Exploring Nuclear Energy Potential for Sustainable Development and Energy Security in Ghana: Challenges, Opportunities and Strategic Imperatives - Rex G. Abrefah; Suleman A. Zakaria; F. Ameyaw (Science and Technology of Nuclear Installations)
This review paper delves into Ghana’s pursuit of nuclear energy as a pivotal component for sustainable development. It highlights the potential benefits of nuclear power in bolstering energy security, stimulating economic growth and advancing environmental sustainability, framed around three core development pillars: economic progress, social advancement and environmental conservation. The paper also discusses the major challenges and critical considerations for nuclear energy adoption, such as financing nuclear projects, managing radioactive waste, upgrading the national electric grid and addressing the social and environmental risks associated with nuclear energy. Through detailed analysis, the study presents the challenges and opportunities that Ghana faces in leveraging nuclear energy for sustainable growth and offers strategic recommendations to guide policymakers and relevant stakeholders.